1997
DOI: 10.1192/bjp.171.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of schizophrenia in Nottingham

Abstract: Methodological considerations call for caution in interpreting such data, but we conclude that the significant fall in the narrowly defined diagnostic category of schizophrenia reflects a real change in the syndromal presentation of psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 16 publications
2
29
0
1
Order By: Relevance
“…However, this was not the case, suggesting that 'nuclear' schizophrenia is more homogeneous and occurs at a very similar frequency in the different populations. In recent years, replications of the design of the WHO ten-country study using the same instruments and procedures have been carried out with very similar results by investigators in India (Rajkumar et al 1993), the Caribbean (Hickling & Rodgers-Johnson 1995;Mahy et al 1999), and the United Kingdom Brewin et al 1997). …”
Section: Incidencementioning
confidence: 84%
See 1 more Smart Citation
“…However, this was not the case, suggesting that 'nuclear' schizophrenia is more homogeneous and occurs at a very similar frequency in the different populations. In recent years, replications of the design of the WHO ten-country study using the same instruments and procedures have been carried out with very similar results by investigators in India (Rajkumar et al 1993), the Caribbean (Hickling & Rodgers-Johnson 1995;Mahy et al 1999), and the United Kingdom Brewin et al 1997). …”
Section: Incidencementioning
confidence: 84%
“…However, the data remain inconsistent or conflicting. Two studies Brewin et al 1997) provide prevalence and incidence data on urban areas that had been surveyed 5 years earlier (inner London) and 12 years earlier (Nottingham). The point prevalence in Hampstead increased from 4.7 per 1000 in 1986 to 5.1 per 1000 in 1991 but the 5-year interval between the two surveys may be too short for detecting any long-term trend.…”
Section: Declining Incidence Of Schizophreniamentioning
confidence: 99%
“…A Nottingham, UK, study examining the incidence of first-episode psychotic disorders in two cohorts, 1978-80 and 1992-4, found that the age-standardised incidence rates for schizophrenia and related disorders was 0.14 per 1000 per year. 33 They found that the rate for all psychoses rose slightly (but not statistically significantly so) but the rate for schizophrenia only had a significant decline. This suggested that an apparent reduction in schizophrenia incidence over time was likely to be due to the range of other psychosis diagnoses being made in the later cohort.…”
Section: Incidence Of Psychosismentioning
confidence: 99%
“…This suggested that an apparent reduction in schizophrenia incidence over time was likely to be due to the range of other psychosis diagnoses being made in the later cohort. 33 A study of the annual incidence of schizophrenia and non-affective psychosis in London found a rate of 0.22 per 1000 [95% confidence interval (CI) 0.15 to 0.29 per 1000]. 34 In a recent Irish study, the annual incidence of all psychoses in people aged over 15 years was estimated to be 0.32 per 1000.…”
Section: Incidence Of Psychosismentioning
confidence: 99%
See 1 more Smart Citation